Penggemar Nike Ardilla, antara Fanatisme dan Eksistensi Diri - Riana Qurniati; Ratna Permata Sari (Program Studi Ilmu Komunikasi UII, 2021)
Nike Ardilla is a phenomenon. Even though she has passed away, the popularity of this female singer seems to have not faded since the 90s. This study examines how the fanaticism of Nike Ardilla fans at the Nike Ardilla Fans Club (NAFC) Jogja Central Java, and how the self-existence of Nike Ardilla fans in Jogja Central Java, is described. This study uses a qualitative descriptive method. Researchers collected data by conducting participant observations and interviews with six informants who have joined the NAFC Jogja Central Java with the snowball technique. The results showed that the fanaticism of Nike Ardilla fans made them unable to separate reality from fantasy. As for the description of self-existence, adult fans are more obsessed and have a higher self-existence compared to young fans, both in the online and offline world.Keywords: Fans, Fandom, Fanatism, Self-Existence